Heterogeneity in risky choice behaviour in a broad population - Hans-Martin von Gaudecker; Arthur van Soest; Erik Wengström (Institute for the Study of Labor (IZA), 2009)
We analyse risk preferences using an experiment with real incentives in a representative sample of 1,422 Dutch respondents. Our econometric model incorporates four structural parameters that vary with observed and unobserved characteristics: Utility curvature, loss aversion, preferences towards the timing of uncertainty resolution, and the propensity to choose randomly rather than on the basis of preferences. We find that all four parameters contribute to explaining choice behaviour. The structural parameters are significantly associated with socio-economic variables, but it is essential to incorporate unobserved heterogeneity in each of them to match the rich variety of choice patterns in the data.
urn:nbn:de:101:1-20090304791
Keywords: C90; D81; 330; Risk aversion; loss aversion; uncertainty resolution; field experiments; Risikopräferenz; Entscheidung bei Unsicherheit; Test; Niederlande